2009
DOI: 10.5194/bg-6-2155-2009
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of calcifying and silicifying phytoplankton in relation to environmental and biogeochemical parameters during the late stages of the 2005 North East Atlantic Spring Bloom

Abstract: Abstract. The late stage of the North East Atlantic (NEA) spring bloom was investigated during June 2005 along a transect section from 45 to 66 • N between 15 and 20 • W in order to characterize the contribution of siliceous and calcareous phytoplankton groups and describe their distribution in relation to environmental factors. We measured several biogeochemical parameters such as nutrients, surface trace metals, algal pigments, biogenic silica (BSi), particulate inorganic carbon (PIC) or calcium carbonate, p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 75 publications
3
25
1
Order By: Relevance
“…[23] Introduction of nitrate and silicate during cyclonic eddy events, favor the formation of large (2-200 mm) diatom [Hasle and Syvertsen, 1997] and subsequent blooms. With the depletion of dissolved silicic acid and increased stratification of the surface layer most likely triggers the crash of the diatom bloom, and subsequently leads to cocolithophore dominance [LeBlanc et al, 2009]. Prasanna reported the higher concentrations of silicate (2mM) compared to nitrate (0.5mM) during the cyclonic eddy period in the surface waters and also observed doming of nitrate and silicate isopleths from 50 m to 10 m depth.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Introduction of nitrate and silicate during cyclonic eddy events, favor the formation of large (2-200 mm) diatom [Hasle and Syvertsen, 1997] and subsequent blooms. With the depletion of dissolved silicic acid and increased stratification of the surface layer most likely triggers the crash of the diatom bloom, and subsequently leads to cocolithophore dominance [LeBlanc et al, 2009]. Prasanna reported the higher concentrations of silicate (2mM) compared to nitrate (0.5mM) during the cyclonic eddy period in the surface waters and also observed doming of nitrate and silicate isopleths from 50 m to 10 m depth.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, major efforts have been dedicated to elucidating the mechanisms that trigger phytoplankton blooms and lead to temporal and spatial phytoplankton species successions in the ocean (Leblanc et al 2009, Mahadevan et al 2012. Although those studies have shown that a combination of ambient physical and chemical conditions could favor the predominance of certain algae at specific times and/or locations, they have also shown that, with the exception of iron requirements (Boyd et al 2000), nutritional requirements are similar across all algae (Redfield 1958).…”
Section: B Vitamins As Biologically Active Compounds In the Oceanmentioning
confidence: 97%
“…Rather, the particular transformation products produced appears to depend on the species of phytoplankton (Bale et al, 2011;Hallegraeff, 1981;Jeffrey and Hallegraeff, 1987;Louda et al, 1998Louda et al, , 2002Owens and Falkowski, 1982), the physiochemical environment (Louda et al, 1998(Louda et al, , 2002Yacobi et al, 2001), and, in the case of grazing, on the species of grazer and on whether the grazing is primary or secondary (coprophagy) (Burkill et al, 1987;Gieskes et al, 1991;Goericke et al, 2000;Hallegraeff, 1981). Furthermore, North Atlantic spring diatom blooms are often thought to be terminated by silicic acid limitation (Henson et al, 2006;Leblanc et al, 2009;Savidge et al, 1995), with major export of phytodetrital aggregates taking place upon bloom termination (Billett et al, 1983). However, while many studies have attributed certain chl-a transformation products to terms such as 'cell stress', 'senescence' and 'death', transformation products associated with potentially nutrient-depleted phytodetrital aggregates have not been studied.…”
Section: Introductionmentioning
confidence: 95%